Electrodialysis membrane for hydriodic acid production, bipolar membrane electrodialysis device, and method for producing hydriodic acid
A cation exchange membrane with controlled unsaturated bond content and oxidation-resistant materials addresses durability issues in hydroiodic acid production, ensuring continuous and stable operation.
Patent Information
- Application Number
- JP2023114605
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-07-12
AI Technical Summary
The durability of ion exchange membranes used in the production of hydroiodic acid is compromised due to iodine oxidation, leading to decreased production efficiency and purity, with issues such as increased water content, decreased cation selectivity, and mechanical deterioration of the cation exchange membrane.
Development of a cation exchange membrane with specific properties including high porosity, controlled unsaturated bond content, and use of oxidation-resistant materials to maintain membrane integrity and stability during hydroiodic acid production.
The proposed membrane design ensures continuous and stable production of hydroiodic acid by preventing membrane deterioration, maintaining high purity and efficiency.
Smart Images

Figure 2025012066000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrodialysis membrane for producing hydroiodic acid, an electrodialysis apparatus equipped with the same, and a method for producing hydroiodic acid using the same. [Background technology]
[0002] Various developments have been made so far regarding technologies for separating iodine from waste liquid containing iodine and methods for using the separated iodine. For example, Patent Document 1 discloses a method for producing hydroiodic acid, in which potassium iodide is concentrated from waste liquid containing iodine and potassium by electrodialysis, and then this concentrated potassium iodide is separated into hydroiodic acid and an aqueous potassium hydroxide solution by bipolar membrane electrodialysis. According to this method, iodine and boron are respectively separated from waste liquid generated during the production of polarizing films and the like by electrodialysis, and hydroiodic acid is produced from potassium iodide by bipolar membrane electrodialysis. Therefore, it is said that hydroiodic acid can be produced using iodine contained in the waste liquid as a raw material, and boron in the waste liquid can also be concentrated, separated, and efficiently recovered. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2009-23847 A Summary of the Invention [Problem to be solved by the invention]
[0004] The method described in Patent Document 1 is an excellent method for producing hydroiodic acid from waste liquid containing iodine with high efficiency and low cost without going through many steps. On the other hand, according to the study by the present inventors, it was found that the durability of the ion exchange membrane is an issue in the latter step of separating concentrated potassium iodide into hydroiodic acid and potassium hydroxide aqueous solution by bipolar membrane electrodialysis. That is, when hydroiodic acid is produced continuously by the above method, liquid movement gradually begins to progress between the alkaline chamber and the salt chamber, and as a result, not only the production efficiency of the potassium hydroxide aqueous solution decreases, but also potassium hydroxide may be mixed from the salt chamber into the hydroiodic acid chamber, resulting in a decrease in the purity of the hydroiodic acid obtained. At this time, when the electrodialysis tank was disassembled and the characteristics of each ion exchange membrane were evaluated, the cation exchange membrane separating the alkaline chamber and the salt chamber showed significant changes in membrane characteristics such as a decrease in electrical resistance, an increase in water content, a decrease in cation selectivity, and a decrease in mechanical strength. Such deterioration occurred from the alkaline liquid side of the cation exchange membrane. Furthermore, after a long period of operation, a phenomenon occurs in which the ion exchange resin mass is peeled off from the membrane, and the membrane function is impaired, which makes it difficult to continuously produce hydroiodic acid. The present invention has been made in view of the above, and an object of the present invention is to provide a cation exchange membrane for electrodialysis that is resistant to the oxidizing power of oxidized iodine, which will be described later, so that hydroiodic acid can be continuously and stably produced. [Means for solving the problem]
[0005] The present inventors have conducted extensive research into the above-mentioned deterioration of cation exchange membranes and have hypothesized the following deterioration mechanism related to iodine, which is the target of treatment. - ) is relatively easily oxidized by various factors such as light, heat, and contact with oxygen to generate iodine molecules (I2). When the iodine molecules diffuse through the cation exchange membrane and enter the alkaline chamber, they immediately turn into iodate ions IO3, which have a high oxidizing power. - and periodate ion IO4 -At this time, if the cation exchange membrane contains, as a component, rubber or the like having unsaturated bonds that have low resistance to oxidative attack, these unsaturated bonds are oxidatively attacked by iodate ions and / or periodate ions, easily causing main chain scission. If main chain scission occurs to a certain extent or more, the rubber component becomes low in molecular weight, peels off from the membrane body of the cation exchange membrane, becomes porous, and finally ceases to function as a diaphragm.
[0006] The present inventors have further carried out research based on the above-mentioned assumed mechanism, and have found that the deterioration behavior can be examined with good reproducibility by using an aqueous periodate solution as an oxidizing agent. Furthermore, in a deterioration test of a cation exchange membrane using an aqueous periodate solution, they have found that the oxidation resistance of the cation exchange membrane can be improved and hydroiodic acid can be stably produced by controlling the content of the unsaturated bonds and other membrane properties. This has led to the completion of the present invention.
[0007] According to one aspect of the present invention, there are provided the following electrodialysis membrane for producing hydroiodic acid, electrodialysis apparatus, and method for producing hydroiodic acid.
[0008] 1. An electrodialysis membrane for producing hydroiodic acid, comprising a cation exchange membrane used in an electrodialysis apparatus for producing hydroiodic acid, The cation exchange membrane is A highly voided substrate; A cation exchange resin phase filled in the voids of the highly porous substrate, The cation exchange membrane has a burst strength retention rate of 70% or more, as measured according to the sodium periodate immersion test described below. Electrodialysis membrane for the production of hydroiodic acid. (Sodium periodate immersion test) Using the cation exchange membrane, a membrane with a surface area of 25 cm 2 Prepare a sheet sample of The sheet sample is subjected to an immersion treatment in which the sheet sample is immersed in a saturated NaIO4 aqueous solution adjusted to a liquid temperature of 40° C. and a pH of 12 for 30 days. The Mullen burst strength (MPa) of the sheet sample before the immersion treatment and the sheet sample after the immersion treatment are measured in accordance with JIS P8112 and designated as S0 and S30, respectively. However, the sheet sample after the immersion treatment is used for the measurement without being dried after being washed with ion-exchanged water. Using the measured value of the Mullen burst strength thus obtained, the burst strength retention rate of the cation exchange membrane is calculated according to the following formula. Bursting strength retention rate (%)=(S30 / S0)×100 2. The cation exchange membrane according to 1., The electrodialysis membrane for producing hydroiodic acid, wherein the cation exchange resin phase does not contain, as a polymer component other than the cation exchange resin, a polymer having an iodine value of 23 mg / 100 mg or more as measured in accordance with JIS-K0070 (1992). 3. A cation exchange membrane according to 1. or 2., An electrodialysis membrane for producing hydroiodic acid, wherein the highly porosity substrate is made of polyolefin or fluororesin. 4. A cation exchange membrane according to any one of 1. to 3., The electrodialysis membrane for producing hydroiodic acid, wherein the water content of the cation exchange membrane is 30% or less, as measured by the following procedure. (Procedure for measuring moisture content) The cation exchange membrane is immersed in a 1 mol / L-NaCl aqueous solution for 4 hours or more, and then thoroughly washed with ion-exchanged water. After that, the moisture on the surface is wiped off with tissue paper, and the mass W (g) of the wet membrane is measured. Furthermore, it is dried under reduced pressure at 60°C for 5 hours and the weight when dry, D (g), is measured. Based on the measured mass value, the water content of the cation exchange membrane is calculated according to the following formula. Moisture content (%)=100×(WD) / D 5. A cation exchange membrane according to any one of 1. to 4., An electrodialysis membrane for producing hydroiodic acid, wherein the porosity of the highly porous substrate is 20% or more and 90% or less, as measured according to the following procedure. (Procedure for measuring void ratio) A rectangular sample of X cm × Y cm is cut out from the highly porous substrate, and the thickness T (μm) of the sample is measured using a micro thickness gauge (terminal diameter Φ: 5 mm, measurement pressure: 62.47 kPa). The mass M (g) of the sample is also measured, and these measurements and the density ρ (g / cm) of the resin material of the highly porous substrate are compared. 3 ) to calculate the porosity (%) of the highly porous substrate using the following formula: Porosity (%)={1-(10000×M / ρ) / (X×Y×T)}×100 6. A cation exchange membrane according to any one of 1. to 5., The electrodialysis membrane for producing hydroiodic acid, wherein the electrodialysis apparatus is a bipolar membrane electrodialysis apparatus. 7. An electrodialysis apparatus for producing hydroiodic acid, comprising: An electrodialysis apparatus comprising, as a cation exchange membrane, the electrodialysis membrane for producing hydroiodic acid according to any one of 1. to 6. 8. The electrodialysis apparatus according to 7., The electrodialysis device is a bipolar membrane electrodialysis device. 9. A method for producing hydroiodic acid, comprising a step of separating an aqueous iodide salt solution into hydroiodic acid and an aqueous hydroxide salt solution using an electrodialysis apparatus equipped with the electrodialysis membrane for producing hydroiodic acid according to any one of 1. to 6. as a cation exchange membrane. 10. The method for producing hydroiodic acid according to 9., the electrodialysis apparatus is a bipolar membrane electrodialysis apparatus, The bipolar membrane electrodialysis apparatus includes the cation exchange membrane, an anion exchange membrane, and a bipolar membrane disposed between the cation exchange membrane and the anion exchange membrane. 11. A method for producing hydroiodic acid according to 9. or 10., comprising the steps of: The method for producing hydroiodic acid, wherein the aqueous iodide salt solution is an aqueous solution containing at least one of an alkali metal iodide salt and an alkaline earth metal iodide salt. Effect of the Invention
[0009] According to the present invention, there are provided an electrodialysis membrane for producing hydroiodic acid which can be used continuously and stably, an electrodialysis apparatus incorporating the same, and a method for producing hydroiodic acid. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a flow diagram showing an example of a method for producing hydroiodic acid. [Diagram 2] FIG. 1 is a diagram illustrating an example of the configuration of a bipolar electrodialysis device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In all drawings, similar components are given similar reference numerals and their explanations will be omitted as appropriate. Also, the drawings are schematic diagrams and do not correspond to the actual dimensional ratios.
[0012] <Electrodialysis membrane for hydroiodic acid production> The electrodialysis membrane for producing iodic acid of the present invention will be outlined below.
[0013] The electrodialysis membrane for producing iodic acid of the present invention is a cation exchange membrane used in an electrodialysis apparatus for producing hydroiodic acid. This cation exchange membrane has a highly porous substrate and a cation exchange resin phase filled in the pores of the highly porous substrate, and satisfies a burst strength retention rate of 70% or more as measured according to the sodium periodate immersion test described below. [Sodium periodate immersion test] A cation exchange membrane is used to measure the surface area of one side of the membrane, which is 25 cm 2 Prepare a sheet sample of The sheet sample is immersed in a saturated NaIO4 aqueous solution adjusted to a liquid temperature of 40° C. and a pH of 12 for 30 days (immersion treatment). The Mullen burst strength (MPa) of the sheet sample before the immersion treatment and the sheet sample after the immersion treatment are measured in accordance with JIS P8112 and designated as S0 and S30, respectively. However, the sheet sample after the immersion treatment is used for the measurement without being dried after being washed with ion-exchanged water. Using the measured value of the Mullen burst strength obtained, the above-mentioned burst strength retention is calculated based on the formula: S30 / S0×100. The burst strength retention must be 70% or more, and is preferably 80% or more. When the burst strength retention is 70% or more, degradation of the cation exchange membrane is suppressed and continuous stable operation is possible when producing hydroiodic acid by electrodialysis. The burst strength retention is usually less than 97%. This is because a membrane with too high a burst strength retention tends to have very high membrane resistance and is not suitable for practical use.
[0014] In the cation exchange membrane used in the present invention, the highly porous substrate may be any known substrate for ion exchange membranes, and generally, a porous support material having a porosity of 20 to 90%, more preferably 30 to 75%, and more preferably 40 to 55% is used. As the material for these highly porous substrates, any substrate that is resistant to alkali and oxidation can be used without limitation, taking into consideration that the cation exchange membrane comes into contact with high-concentration alkali such as potassium hydroxide during the production of iodic acid and that resistance to the oxidation of the generated iodate ions and / or periodate ions is required.
[0015] Specifically, for example, substrates made of polyolefin or fluororesin can be used, and from the viewpoint of oxidation resistance, fluorine-containing resins such as polytetrafluoroethylene, polychlorotrifluoroethylene, and poly(tetrafluoroethylene-perfluoroalkyl ether) can be suitably used. In particular, from the viewpoint of affinity with ion exchange resins and chemical resistance, polyolefins such as polypropylene and polyethylene are preferred, and polyethylene is more preferred. When a substrate made of polyvinyl chloride is used, even if it has excellent oxidation resistance, it is not preferred because the vinyl chloride resin is dechlorinated by contact with high concentration alkali, resulting in a decrease in strength. The thickness of the substrate is generally selected from the range of 50 to 300 μm, and is preferably 70 to 250 μm from the viewpoint of membrane resistance and strength retention.
[0016] In addition, the form of the highly porous substrate may be, without limitation, a woven fabric, a nonwoven fabric, a porous film, a mesh material, etc., but it is preferable to use a woven fabric or a mesh material, since it is easy to increase the strength of the resulting cation exchange membrane and a cation exchange membrane having excellent dimensional stability can be obtained.
[0017] Here, in the cation exchange membrane having a cation exchange resin phase filled in the voids of the highly porous substrate, the cation exchange resin portion generally contains various other polymer components in addition to the ion exchange resin as the main component. For example, polymer thickeners added for the purpose of adjusting the viscosity of the precursor composition of the cation exchange resin, polymeric hydrochloric acid scavenger for scavenging hydrogen chloride generated in the polymerization process, polymeric flexibility imparting agents for imparting flexibility to the cation exchange membrane, polymeric plasticizers, and other polymer additives are mixed or remain. Thus, for these polymer additives, polymers having unsaturated bonds in the main chain are often used for the purpose of increasing the solubility in the cation exchange resin precursor composition or increasing the flexibility of the membrane.
[0018] In particular, the cation exchange membrane used in the present invention is exclusively manufactured by the paste method described below. In that case, when the highly porous substrate is a woven fabric, a nonwoven fabric, or a net (hereinafter, abbreviated as "woven fabric, net, etc."), the voids are exposed not only inside the substrate but also to the surface with large openings, so it is required to increase the retention of the paste after filling. For this reason, it is essential that a polymer thickener is blended into the paste (cation exchange resin precursor composition) in order to increase the viscosity to a certain level or higher. A polymer having an unsaturated bond in the main chain is used as this polymer thickener. Specifically, styrene-based thermoplastic elastomers such as polystyrene-polybutadiene-polystyrene copolymer and polystyrene-polyisoprene rubber-polystyrene copolymer, acrylonitrile-butadiene rubber, pyridine rubber, etc. are used. That is, these polymers have an iodine value, which is an index of the amount of carbon-carbon unsaturated bonds in the main chain, that exceeds 26 mg / 100 mg and generally has a value of 250 mg / 100 mg or more. The iodine value can be determined according to JIS-K0070 (1992), and a high iodine value means that a corresponding amount of unsaturated bonds remain.
[0019] The inventors have found that such a polymer having a large amount of unsaturated bonds is prone to oxidation by the iodate ion IO3 - and periodate ion IO4 - In other words, it was found that the main reason why the burst strength retention rate of the above-mentioned cation exchange membrane does not satisfy the requirement of 70% or more in the sodium periodate immersion test is that the cation exchange resin contains a significant amount of such polymers with a large amount of unsaturated bonds. Therefore, the cation exchange membrane having the burst strength retention rate of 70% or more can be obtained by not containing the polymer having the iodine value of 26mg / 100mg or more. In other words, when the polymer additive is blended into the cation exchange membrane, it is necessary to use a polymer having an iodine value of less than 26mg / 100mg. If the cation exchange membrane has a burst strength retention rate of 80% or more, it is preferable to not contain the polymer having an iodine value of 23mg / 100mg or more, and therefore it is necessary to use a polymer additive having an iodine value of less than 23mg / 100mg.
[0020] The cation exchange membrane used in the present invention is preferably free of polymers having an iodine value of 26 mg / 100 mg or more. The above-mentioned "free" does not only mean that the polymers having the iodine value are not contained at all, but also that the polymers are contained in such a small amount that does not affect the value of the burst strength retention rate. Specifically, the amount of the polymers contained is 2.0 parts by mass or less, more preferably 0.5 parts by mass or less, in 100 parts by mass of the cation exchange resin phase (i.e., the components excluding the high-porosity substrate).
[0021] As the polymer additive having a low iodine value, for example, if it is used as a polymer thickener, resins having substantially no unsaturated bonds, such as polyvinyl chloride, chlorinated polyvinyl chloride, ethylene-vinyl chloride copolymer, vinyl chloride-based elastomer, polyethylene, polypropylene, chlorinated polyethylene, chlorosulfonated polyethylene, ethylene-propylene copolymer, saturated aliphatic hydrocarbon-based polymer such as polybutylene, etc., can be used. In addition, styrene-based thermoplastic elastomers such as polystyrene-polybutadiene-polystyrene copolymer and polystyrene-polyisoprene rubber-polystyrene copolymer, nitrile rubber, and pyridine rubber can be used by adjusting the iodine value to less than 26 mg / 100 mg, preferably less than 23 mg / 100 mg, by hydrogenation.
[0022] The molecular weight of such polymer additives is not particularly limited, but is usually preferably in the range of 1,000 to 1,000,000, and particularly preferably 50,000 to 500,000.
[0023] In the cation exchange membrane of the present invention, the polymer additive is preferably contained in an amount of 65 parts by mass or less, more preferably 55 parts by mass or less, per 100 parts by mass of the cation exchange resin phase, i.e., the components excluding the highly voided substrate. When the highly voided substrate is a woven fabric, a net-like material, or the like, a polymer thickener is blended in the paste (cation exchange resin precursor composition), so that the content of the polymer additive is preferably 3% by mass or more, more preferably 5% by mass or more.
[0024] On the other hand, when the polymer substrate of the cation exchange membrane is a porous film, if it is manufactured by the paste method, in order to increase the filling ability of the paste into the voids, it is necessary to increase the permeability of the paste into the pores on the film surface. For this reason, it is desirable to suppress the blending amount of the polymer thickener into the paste to a small amount, and in some cases, no polymer thickener is blended. In this way, even if the polymer substrate is a porous film and the blending amount of the polymer thickener is small or no, it is easy to make the polymer with an iodine value of 26 mg / 100 mg or more non-containing, and it is possible to obtain a cation exchange membrane with a burst strength retention rate of 70% or more.
[0025] The average pore size of the porous film is preferably 0.01 to 2.0 μm, and more preferably 0.015 to 0.4 μm.
[0026] The cation exchange resin of the present invention can be any cation exchange resin used in a conventionally known cation exchange membrane without any restrictions. That is, fluorine-based cation exchange resins such as perfluorocarbon sulfonic acid, resins in which a sulfonic acid group is introduced into a copolymer such as a styrene-divinylbenzene-based resin, a hydrocarbon-based cation exchange resin obtained by polymerization of (meth)acrylic acid, and even resins in which a cation exchange group is introduced into an engineering plastic such as polysulfone or polyethersulfone are used. In particular, styrene-divinylbenzene-based resins are preferred in that they have excellent oxidation resistance, high affinity with the highly porous substrate, and can exhibit excellent cation selectivity. Any known exchange group can be used as the cation exchange group, but a sulfonic acid group is preferred in that they have excellent oxidation resistance and can reduce electrical resistance.
[0027] The above-mentioned cation exchange membrane in the present invention may be produced by any method as long as it satisfies the above requirements, and can be produced, for example, by preparing a resin solution in which a fluorine-based cation exchange resin such as a perfluoroalkylsulfonic acid resin or a hydrocarbon-based cation exchange resin in which a sulfonic acid group has been introduced into a polystyrene-based resin as necessary is dissolved or dispersed in an organic solvent, and then immersing or casting this solution on a highly porous substrate and drying it. The following method is preferable in that a dense cation exchange resin portion can be formed and high properties such as ion selectivity can be obtained. That is, this is a manufacturing method (paste method) in which a paste of a polymerizable composition is prepared as a cation exchange resin precursor composition (preparation of polymerizable composition), the polymerizable composition is filled into the voids of the highly porous substrate (filling of polymerizable composition), the polymerizable composition filled in the voids is then polymerized, and, if necessary, cation exchange groups are introduced into the polymer (cation exchange resin precursor) obtained in the polymerization process (ion exchange group introduction process).
[0028] 1. Polymerizable composition preparation; The polymerizable composition for forming a cation exchange resin contains a monomer having a functional group capable of introducing a cation exchange group (functional group for introducing a cation exchange group) or a monomer having a cation exchange group (hereinafter, these monomers may be referred to as "basic monomer components"), a crosslinking monomer, and a polymerization initiator, and is prepared by mixing these components.
[0029] The monomer having a functional group for introducing a cation exchange group and the monomer having a cation exchange group may be any monomer that has been conventionally used for producing a cation exchange resin.
[0030] For example, examples of monomers having a functional group for introducing a cation exchange group include styrene, vinyl toluene, vinyl xylene, α-methyl styrene, vinyl naphthalene, and α-halogenated styrenes.
[0031] Examples of monomers having a cation exchange group include sulfonic acid monomers such as α-halogenated vinyl sulfonic acid, styrene sulfonic acid, and vinyl sulfonic acid; carboxylic acid monomers such as methacrylic acid, acrylic acid, and maleic anhydride; phosphonic acid monomers such as vinyl phosphoric acid; and salts and esters thereof.
[0032] When a monomer having a cation exchange group is used as the above-mentioned monomer, the desired cation exchange membrane can be obtained at the stage when the polymerization step described below is completed. However, when a monomer having a functional group for introducing a cation exchange group is used, the desired cation exchange membrane can be obtained by carrying out a cation exchange group introduction step after the polymerization step.
[0033] The crosslinkable monomer is used to densify the cation exchange resin to increase ion selectivity, or to increase swelling inhibition and membrane strength, and is not particularly limited. Examples of the crosslinkable monomer include compounds having a plurality of vinyl groups, such as divinylbenzene, divinyl sulfone, butadiene, chloroprene, divinyl biphenyl, trivinylbenzenes, divinyl naphthalene, diallylamine, and divinyl pyridine, and compounds having a halogenated alkyl group, such as chloromethyl styrene, chloroethyl styrene, and bromobutyl styrene. Generally, the amount of such a crosslinkable monomer is preferably 5 to 50 parts by mass, more preferably 10 to 40 parts by mass, relative to 100 parts by mass of the total monomer components. When a porous film is used as the highly porous substrate, the amount is preferably 25 to 50 parts by mass, more preferably 30 to 40 parts by mass. If the amount is less than 5 parts by mass, the oxidation resistance against iodine is insufficient, while if the amount exceeds 50 parts by mass, the membrane resistance increases extremely, making it difficult to use in electrodialysis.
[0034] In addition to the above-mentioned monomer having a functional group for introducing an exchange group, monomer having an ion exchange group, and crosslinkable monomer, other monomers copolymerizable with these monomers may be added as necessary. Examples of such other monomers include acrylonitrile, acrolein, methyl vinyl ketone, and vinyl biphenyl.
[0035] The polymerization initiator may be any of the conventionally known ones without any particular limitation.Specific examples of the polymerization initiator include organic peroxides such as octanoyl peroxide, lauroyl peroxide, t-butyl peroxy-2-ethylhexanoate, benzoyl peroxide, t-butyl peroxyisobutyrate, t-butyl peroxylaurate, t-hexyl peroxybenzoate, and di-t-butyl peroxide. The amount of such a polymerization initiator is preferably 0.1 to 20 parts by weight, and more preferably 0.5 to 10 parts by weight, based on 100 parts by weight of the total of the monomer components.
[0036] In order to adjust the permeability into the highly porous substrate and improve compatibility, the polymeric thickener is generally blended into the polymerizable composition containing the above-mentioned various components. In particular, when the highly porous substrate is a woven fabric, a net-like material, etc., as described above, the blending of the above-mentioned polymeric thickener is essential to increase the filling and retention force of the paste into the voids. When such a polymer thickener is blended in the polymerizable composition, it is preferably blended in an amount of up to 185 parts by mass, more preferably up to 120 parts by mass, per 100 parts by mass of the total monomer components. When the highly void substrate is a woven fabric, net, or the like, and the polymer thickener is blended in the polymerizable composition, it is preferably blended in an amount of 3.3 parts by mass or more, more preferably 5.5 parts by mass or more, per 100 parts by mass of the total monomer components.
[0037] 2. Filling with a polymerizable composition; The filling of the voids in the highly porous substrate is carried out, for example, by immersing the substrate in a tank filled with the polymerizable composition described above. By this immersion, a cation exchange membrane precursor in which the polymerizable composition is filled in the voids in the highly porous substrate is obtained. Of course, the polymerizable composition can be filled by spray coating instead of immersion.
[0038] 3. Polymerization; The cation exchange membrane precursor in which the pores of the highly porous substrate are filled with the polymerizable composition as described above is heated and polymerized in a polymerization apparatus such as a heating oven. When a monomer having a cation exchange group is used as the basic monomer component, the desired cation exchange membrane is obtained upon completion of this step. When a monomer having a functional group for introducing an exchange group is used as the basic component, the introduction of the cation exchange group is required after completion of this step.
[0039] In this polymerization step, a method is generally adopted in which the cation exchange membrane precursor filled with the polymerizable composition is sandwiched between films such as polyester and the like and heated from room temperature under pressure. Pressurization is generally performed at a pressure of about 0.1 to 1.0 MPa by applying an inert gas such as nitrogen or by using a roll or the like. This pressurization allows polymerization to be performed in a state in which the excess polymerizable composition present at the outer interface of the substrate is pushed into the voids of the substrate, and the occurrence of resin pools can be effectively prevented. The polymerization conditions depend on the type of polymerization initiator, the type of monomer, etc., and may be appropriately selected from known conditions.
[0040] When the highly porous substrate is made of an olefin resin, the polymerization temperature may be set to a temperature lower than the melting point of the olefin resin, and is generally in the range of about 40 to 130° C. in the case of a polyethylene film. The polymerization time varies depending on the polymerization temperature, etc., but is generally about 3 to 20 hours.
[0041] 4. Introduction of cation exchange groups; As mentioned above, when a monomer having a cation exchange group is used as the basic monomer component in the polymer composition, a cation exchange resin is formed by the above-mentioned polymerization step, and the desired cation exchange membrane is obtained at this stage. However, when a monomer having a functional group for introducing a cation exchange group is used as the basic monomer component, the resin obtained in the above-mentioned polymerization step does not have a cation exchange group, so that it is necessary to introduce the cation exchange group after the polymerization step.
[0042] The introduction of a cation exchange group is carried out by a method known per se, for example, by a treatment such as sulfonation, chlorosulfonation, phosphonium conversion, hydrolysis, etc. The cation exchange membrane of the present invention obtained as described above has a water content of usually 35% or less, preferably 30% or less, by selecting an appropriate high-porosity substrate and polymer additive, and adjusting the amount of crosslinkable monomer. This water content enhances the oxidation resistance to oxidized iodine. The water content is usually 10% or more, preferably 15% or more, so that the membrane resistance does not become extremely high. The cation exchange capacity is preferably in the range of 0.5 to 3.0 meq / g-dry membrane, particularly 0.8 to 2.0 meq / g-dry membrane, and the electrical resistivity is preferably 1.5 Ω cm 2 More than 15.0Ω cm 2 Less than or equal to 2.5 Ω cm 2 More than 12.0Ω cm 2 It is preferable that the Mullen burst strength is within the following range. The Mullen burst strength is usually 0.30 MPa or more, preferably 0.35 to 2.0 MPa. The thickness is adjusted to be within the range of 50 to 320 μm, particularly 70 to 280 μm. Here, when the highly porous substrate is a woven fabric, a net, or the like, the substrate has excellent mechanical strength as described above, so that a high Mullen burst strength of 0.5 to 2.0 MPa is easily obtained. On the other hand, when the highly porous substrate is a porous film, the Mullen burst strength is usually 0.30 to 0.60 MPa.
[0043] <How to manufacture hydroiodic acid> Next, a method for producing hydroiodic acid using an electrodialysis apparatus including the above-mentioned electrodialysis membrane for producing hydroiodic acid as a cation exchange membrane will be described. As the electrodialysis device, it is preferable to use a bipolar electrodialysis device, but the present invention is not limited to this.
[0044] Fig. 1 is a flow diagram showing an example of a method for producing hydroiodic acid. Fig. 2 is a schematic diagram showing an example of the configuration of a bipolar electrodialysis device 1.
[0045] As shown in Fig. 2, the bipolar membrane electrodialysis device 1 has a membrane structure in which cation exchange membranes 4k and anion exchange membranes 4a are alternately arranged between the anode 2 and the cathode 3, and a bipolar membrane 4b is arranged between them. In the membrane structure, the cation exchange membrane 4k, the bipolar membrane 4b, and the anion exchange membrane 4a are arranged in this order from the anode 2 side to the cathode 3 side. However, the membrane arranged closest to the electrode is not limited to the cation exchange membrane 4k, and may be the bipolar membrane 4b. The bipolar membrane electrodialysis device 1 is not limited to that shown in FIG. 2, and may have a known device configuration.
[0046] The bipolar membrane 4b is a laminate of a cation exchange membrane and an anion exchange membrane, one surface of which acts as a cation exchange membrane and the other surface of which acts as an anion exchange membrane. The above-mentioned electrodialysis membrane for producing hydroiodic acid is used for part or all of the cation exchange membranes mounted in the bipolar membrane electrodialysis device 1.
[0047] An electrode solution is supplied from an electrode solution tank (not shown) to the electrode chamber (anode chamber) containing the anode 2 and the electrode chamber (cathode chamber) containing the cathode 3. The anode chamber and the cathode chamber are disposed on either side of the electrodialysis cell. When a current is applied to the anode 2 and the cathode 3 using a power source, electrodialysis begins in the electrodialysis cell.
[0048] As the electrode solution, a known solution can be used, such as an aqueous solution of sodium hydroxide, an aqueous solution of potassium hydroxide, an aqueous solution of sodium hydrogen sulfate, or an aqueous solution of potassium sulfate.
[0049] The electrodialysis cell has an acid chamber, a desalting chamber, and an alkaline chamber. The acid chamber is a compartment separated by a bipolar membrane 4b and an anion exchange membrane 4a, the desalting chamber is a compartment separated by an anion exchange membrane 4a and a cation exchange membrane 4k, and the alkaline chamber is a compartment separated by a cation exchange membrane 4k and a bipolar membrane 4b. The bipolar membrane electrodialysis device 1 may have one or more acid chambers, but may have two or more acid chambers from the viewpoint of increasing the treatment capacity.
[0050] An example of the operation of the bipolar membrane electrodialysis device 1 during electrodialysis is as follows. An aqueous iodide salt solution (for example, a KI concentrate) is introduced into the bipolar membrane electrodialysis device 1. Specifically, the KI concentrate is supplied to a deionization compartment between the anion exchange membrane 4a and the cation exchange membrane 4k. Next, with the electrode solution being supplied to the anode 2 and the cathode 3, a direct current is applied between the anode 2 and the cathode 3. This dissociates the iodide salt in the iodide salt solution, and hydroiodic acid (aqueous solution in which hydrogen iodide is dissolved in water) and a hydroxide salt solution are discharged. For example, when the KI concentrated solution is dissociated, the HI solution is discharged from the acid compartment, and the KOH solution is discharged from the alkaline compartment. Thereafter, the discharged hydroiodic acid such as the HI liquid may be purified by distillation or the like.
[0051] An example of a chemical reaction that occurs in the bipolar membrane electrodialysis device 1 during electrodialysis is as follows. Anion (I - ) permeates the anion exchange membrane 4a and is split into H ions (H + ) to form an acid (HI). On the other hand, the cation (K + ) permeates the cation exchange membrane 4k and is split into OH ions (OH - ) to produce alkali (KOH).
[0052] Before electrodialysis, the acid compartment, the deionization compartment, and the alkali compartment may each contain various electrolytic solutions. The electrolytic solution may contain, for example, an aqueous solution of an inorganic salt having electrical conductivity. For example, when the bipolar membrane electrodialysis device 1 is used for the first time, ion-exchanged water may be used.
[0053] The aqueous iodide salt solution is not limited to an aqueous potassium iodide solution (KI concentrate), but may be an aqueous solution containing at least one of an alkali metal iodide salt and an alkaline earth metal iodide salt. Examples of the alkali metal iodide salt include potassium iodide, sodium iodide, cesium iodide, etc. Examples of the alkaline earth metal iodide salt include calcium iodide, magnesium iodide, etc. These may be used alone or in combination of two or more. If necessary, the aqueous iodide salt solution may be acidified by adjusting the pH to less than 7 prior to introduction.
[0054] The aqueous iodide salt solution may be an iodine-containing concentrated solution obtained by electrodialysis of a waste liquid containing an iodine component using an electrodialysis device equipped with a concentration compartment and a desalting compartment. The waste liquid is not particularly limited as long as it is a liquid containing an iodine component, but examples thereof include waste liquid discharged from the manufacturing process of a product containing an iodine component, waste liquid discharged during disposal of a product containing an iodine component, waste liquid discharged from a synthesis process using an iodine component as a reaction catalyst, and waste cleaning liquid used to clean manufacturing equipment that uses an iodine component.
[0055] Specific examples of raw materials for waste liquid include waste liquid, waste powder, and waste solids from the manufacturing process, manufacturing equipment, or waste materials of products containing iodine components such as polarizing films, contrast agents, disinfectants, and radiation-related materials, or waste liquid or waste solids containing iodine catalysts (organic iodine compounds or inorganic iodine compounds) used in chemical synthesis such as the synthesis of pharmaceuticals such as antibiotics and antiviral agents. These may be used alone or in combination of two or more.
[0056] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. EXAMPLES
[0057] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the descriptions of these examples.
[0058] <Manufacture of electrodialysis membranes (cation exchange membranes) for hydroiodic acid production> The physical properties of the cation exchange membranes in the examples and comparative examples were measured by the following methods.
[0059] 1. Cation exchange capacity and water content of cation exchange membrane The cation exchange membrane is immersed in a 0.5 mol / L-HCl aqueous solution for 10 hours or more. Then, the counter ions of the cation exchange groups were replaced with sodium ions from hydrogen ions using a 0.5 mol / L NaCl aqueous solution, and the amount of liberated hydrogen ions, A (mol), was quantified using a potentiometric titrator (COMTITE-900, manufactured by Hiranuma Sangyo Co., Ltd.) with an aqueous sodium hydroxide solution. Next, the same cation exchange membrane was immersed in a 0.5 mol / L-NaCl aqueous solution for more than 4 hours and thoroughly washed with ion-exchanged water. The surface moisture was then wiped off with tissue paper, and the mass W (g) of the membrane when wet was measured. It was then dried under reduced pressure at 60°C for 5 hours, and the weight D (g) of the membrane when dry was measured. Based on the above measured values, the cation exchange capacity and water content of the cation exchange membrane were calculated according to the following formulas. Cation exchange capacity = A x 1000 / D [meq / g-dry mass] ·Moisture content=100×(WD) / D[%]
[0060] 2. Thickness of the cation exchange membrane The cation exchange membrane was immersed in 0.5 mol / L-NaCl solution for 4 hours or more, after which the moisture on the membrane surface was wiped off with tissue paper and the measurement was performed using a micrometer MED-25PJ (manufactured by Mitutoyo Corporation).
[0061] 3. Membrane resistance of cation exchange membrane A cation exchange membrane was sandwiched between two compartments of a cell with platinum black electrodes, both sides of the cation exchange membrane were filled with 0.5 mol / L-NaCl aqueous solution, and the resistance between the electrodes was measured at 25°C using an AC bridge (frequency 1000 cycles / sec). The membrane resistance was calculated from the difference between the electrode resistance and the electrode resistance without the cation exchange membrane. The ion exchange membrane used in the above measurement was previously equilibrated in a 0.5 mol / L NaCl aqueous solution.
[0062] 4.Porosity of high-porosity substrate A rectangular sample of X cm × Y cm was cut out from the highly porous substrate, and the thickness T (μm) of the sample was measured using a micro thickness gauge (terminal diameter Φ: 5 mm, measurement pressure: 62.47 kPa). The mass M (g) of the sample was also measured, and these measurements and the density ρ (g / cm) of the resin material of the highly porous substrate were compared. 3 ) was used to calculate the porosity (%) of the highly porous substrate according to the following formula. Porosity (%)={1-(10000×M / ρ) / (X×Y×T)}×100
[0063] 5. Average pore size of highly porous substrate The measurements were performed using the half-dry method in accordance with ASTM-F316-86.
[0064] 6. Mullen burst strength of cation exchange membrane: The cation exchange membrane was immersed in a 0.5 mol / L-NaCl aqueous solution for 4 hours or more and thoroughly washed with cation exchange water. Then, without drying the membrane, the Mullen burst strength (MPa) before the sodium periodate immersion test was measured using a Mullen burst tester (manufactured by Toyo Seiki Co., Ltd.) in accordance with JIS-P8112, and the measured value was designated as S0. 7. Sodium periodate immersion test (1) The surface area of one side is 25 cm 2 The sheet sample was immersed in a saturated NaIO4 aqueous solution adjusted to pH 12 at a liquid temperature of 40°C for 30 days, to carry out an immersion treatment. (2) After the sodium periodate immersion test, the sheet samples were measured for Mullen burst strength (MPa) in accordance with JIS P8112, and the measured value was designated as S30. However, after the immersion treatment, the sheet samples were washed with ion-exchanged water and then used for the measurement without drying. (3) Using the measured values S0 and S30 of the Mullen burst strength obtained, the burst strength retention rate of the cation exchange membrane was calculated according to the following formula. Bursting strength retention rate (%)=(S30 / S0)×100
[0065] Example 1 A polymer additive consisting of 60.0 parts by mass of unmodified spherical low-density polyethylene powder (particle size 6 μm, melting point 105° C.), 30.0 parts by mass of polyvinyl chloride powder (average polymerization degree 1050), and a mixture of 6.0 parts by mass of maleic anhydride-modified, hydrogenated styrene-butadiene block copolymer (polystyrene content 30% by mass, iodine value 22 mg / 100 mg, maleic anhydride modification amount=2% by mass) was added to a mixture of 39.7 parts by mass of styrene, 5.2 parts by mass of divinylbenzene, 40.6 parts by mass of p-chloromethylstyrene, 14.5 parts by mass of acrylonitrile, 13.0 parts by mass of acetyl tributyl citrate, and 7.3 parts by mass of 1,1-di(tert-butylperoxy)cyclohexane, and the mixture was stirred for 5 hours to obtain a uniform polymerizable composition. The obtained polymerizable composition was applied onto a high-density polyethylene monofilament woven fabric (high porosity substrate, warp: 96 mesh-wire diameter 106 μm (62 denier), weft: 76 mesh-wire diameter 122 μm (71 denier), thickness 260 μm, opening area 38%, porosity 72%, melting point 130° C.), both sides were covered with polyester film as a release agent, and polymerization was carried out at 95° C. for 5 hours. The obtained membranous polymer was sulfonated with chlorosulfonic acid at 40° C. for 2 hours (formation of a cation exchange resin phase) to obtain a cation exchange membrane.
[0066] The properties of the obtained cation exchange membrane of Example 1 were as follows. Film thickness: 290μm Ion exchange capacity: 1.4meq / g-dry mass ·Moisture content: 30%, ·Membrane resistance: 12.2Ω·cm 2 Mullen burst strength S0: 1.6MPa When the above-mentioned sodium periodate immersion test was carried out using the cation exchange membrane of Example 1, the Mullen burst strength S30 was 1.5 MPa, and the burst strength retention rate was 93%.
[0067] Example 2 A mixture of 43.5 parts by mass of styrene, 36.5 parts by mass of p-chloromethylstyrene, 20.0 parts by mass of acrylonitrile, 10.0 parts by mass of acetyl tributyl citrate, 2.9 parts by mass of ethylene glycol diglycidyl ether, and 1.9 parts by mass of di-tert-butyl peroxide was stirred for 2 hours to obtain a homogeneous polymerizable composition. The obtained polymerizable composition was applied onto a polyethylene biaxially stretched porous film (high porosity substrate, thickness 100 μm, porosity 46%, average pore size 0.13 μm), and both sides were covered with polyester film as a release agent, and then the film was held at 50° C. for 20 minutes, and then heated to 110° C. over 60 minutes and further to 130° C. over 80 minutes, and then held at 130° C. for 3 hours to polymerize. The obtained membrane-like polymer was sulfonated (formation of a cation exchange resin phase) with chlorosulfonic acid at 40° C. for 1.5 hours to obtain a cation exchange membrane.
[0068] The obtained cation exchange membrane of Example 2 had the following characteristics. Film thickness: 106μm Ion exchange capacity: 1.6meq / g-dry mass ·Moisture content: 28% ·Membrane resistance: 3.8Ω·cm 2 Mullen burst strength S0: 0.43MPa When a sodium periodate immersion test was carried out using the cation exchange membrane of Example 2, the Mullen burst strength S30 was 0.37 MPa, and the burst strength retention rate was 86%.
[0069] Comparative Example 1 The procedure of Example 1 was repeated, except that the hydrogenated styrene-butadiene block copolymer was not used, and an acrylonitrile-butadiene rubber (acrylonitrile content: 35% by mass) having an iodine value of 304 mg / 100 mg was used as the polymer additive. The characteristics of the cation exchange membrane of Comparative Example 1 were as follows. Film thickness: 297μm Ion exchange capacity: 1.4meq / g-dry mass ·Moisture content: 32% ·Membrane resistance: 10.5Ω·cm 2 Mullen burst strength S0: 1.6MPa When a sodium periodate immersion test was carried out using the cation exchange membrane of Comparative Example 1, the Mullen burst strength S30 was 0.96 MPa, and the burst strength retention rate was 60%. Comparative Example 2 As the cation exchange membrane, a commercially available membrane (CMB manufactured by ASTOM CORPORATION) containing 12 mass% of a polymer additive with an iodine value of 28 mg / 100 mg in components other than the substrate was used. The characteristics of the cation exchange membrane of Comparative Example 2 were as follows. Film thickness: 201μm Ion exchange capacity: 2.7meq / g-dry mass ·Moisture content: 36% ·Membrane resistance: 10.5Ω·cm 2 Mullen burst strength S0: 0.70MPa When a sodium periodate immersion test was carried out using the cation exchange membrane of Comparative Example 2, the Mullen burst strength S30 was 0.25 MPa, and the burst strength retention rate was 36%.
[0070] <Operation test of electrodialysis equipment for producing hydroiodic acid> A bipolar membrane electrodialysis apparatus (Astrom Corporation, Acilyzer EX3B type) was prepared using a bipolar membrane (Astrom Corporation, Neocepta BP-1E), an anion exchange membrane (Astrom Corporation, ACM), and a cation exchange membrane of each Example and Comparative Example. Using the above bipolar membrane electrodialysis apparatus, 1 L of an aqueous iodide salt solution, the pH of which had been adjusted to 1 or less with hydroiodic acid or hydrochloric acid, was introduced into the salt chamber, and dialysis was performed at a constant voltage of 25 V until the iodide ion concentration of the salt solution reached 30 g / L. The composition of the iodide salt solution introduced into the salt room was 300 g / L iodide ion, 27 g / L sodium, 46 g / L potassium, 0.2 g / L phosphorus, 0.3 g / L sulfate ion, and 30 g / L chloride ion.
[0071] As a result of electrodialysis, in each of the Examples and Comparative Examples, The recovered acid liquid (hydriodic acid) had a hydrogen iodide concentration of 320 g / L and a pH of 1 or less. The total concentration of sodium hydroxide and potassium hydroxide in the recovered alkaline solution (hydroxide salt aqueous solution) was 2 mol / L or more and the pH was 13 or more.
[0072] (Evaluation of composition in alkaline solution) It was confirmed that the phosphorus concentration in the alkaline solution was 10 to 30 mg / L or less in the electrodialysis using the cation exchange membranes of Examples 1 and 2. The phosphorus concentration in the alkaline solution was measured by the standard addition method using an ICP atomic emission spectrometer manufactured by Shimadzu Corporation. On the other hand, in the cases of Comparative Examples 1 and 2, the phosphorus concentration in the alkaline solution was 80 to 200 mg / L. According to the inventors' belief, it is presumed that the shielding effect of the cation exchange membrane in Comparative Examples 1 and 2 was reduced due to oxidizing substances in the alkaline solution, causing the phosphorus components contained in the salt solution to pass through the cation exchange membrane and penetrate excessively into the alkaline solution.
[0073] (Evaluation of salt solution volume loss rate) At the start and end of electrodialysis, the volumes of the salt solution (iodide salt aqueous solution introduced into the salt chamber) were measured and designated as V1 and V2, respectively. Using V1 and V2, the reduction rate (%) of the salt solution volume before and after electrodialysis was calculated by the formula: [(V2-V1) / V1]×100. A reduction rate of the salt solution volume of about 20-30% is usually used as a guideline for stable operation. As a result of the rate of decrease in the amount of the salt solution, Example 1 was 22%, Example 2 was 25%, Comparative Example 1 was 33%, and Comparative Example 2 was 40%. According to the inventors, it is believed that the cation exchange membranes of Comparative Examples 1 and 2 were damaged by oxidizing substances in the alkaline liquid, causing water (circulating liquid) to move violently from the salt chamber to the alkaline chamber.
[0074] An electrodialysis test was carried out to separate an aqueous potassium iodide solution into an aqueous potassium hydroxide solution and an aqueous potassium iodide solution using a bipolar membrane electrodialysis device in which the electrodialysis membranes for producing hydroiodic acid of Examples 1 and 2 were used as cation exchange membranes. As a result, it was found that stable electrodialysis was possible compared to Comparative Examples 1 and 2. [Explanation of symbols]
[0075] 1. Bipolar electrodialysis device 2 Anode 3 cathode 4a Anion exchange membrane 4b Bipolar membrane 4k cation exchange membrane
Claims
1. An electrodialysis membrane for producing hydroiodic acid, comprising a cation exchange membrane used in an electrodialysis apparatus for producing hydroiodic acid, The cation exchange membrane is A highly voided substrate; A cation exchange resin phase filled in the voids of the highly porous substrate, The cation exchange membrane has a burst strength retention rate of 70% or more, as measured according to the sodium periodate immersion test described below. Electrodialysis membrane for the production of hydroiodic acid. (Sodium periodate immersion test) Using the above cation exchange membrane, a membrane having a surface area of 25 cm 2 Prepare a sheet sample of The sheet sample was dissolved in saturated NaIO 4 An immersion treatment is carried out by immersing the sample in the aqueous solution for 30 days. The Mullen burst strength (MPa) of the sheet sample before the immersion treatment and the sheet sample after the immersion treatment are measured in accordance with JIS P8112 and designated as S0 and S30, respectively. However, the sheet sample after the immersion treatment is used for the measurement without being dried after being washed with ion-exchanged water. Using the measured value of the Mullen burst strength thus obtained, the burst strength retention rate of the cation exchange membrane is calculated according to the following formula. Bursting strength retention rate (%) = (S30 / S0) x 100
2. 2. The cation exchange membrane of claim 1 , The electrodialysis membrane for producing hydroiodic acid, wherein the cation exchange resin phase does not contain, as a polymer component other than the cation exchange resin, a polymer having an iodine value of 23 mg / 100 mg or more as measured in accordance with JIS-K0070 (1992).
3. 3. The cation exchange membrane according to claim 1 or 2, An electrodialysis membrane for producing hydroiodic acid, wherein the highly porosity substrate is made of polyolefin or fluororesin.
4. 3. The cation exchange membrane according to claim 1 or 2, The electrodialysis membrane for producing hydroiodic acid, wherein the water content of the cation exchange membrane is 30% or less, as measured by the following procedure. (Procedure for measuring moisture content) The cation exchange membrane is immersed in a 1 mol / L-NaCl aqueous solution for 4 hours or more, and then thoroughly washed with ion-exchanged water. After that, the moisture on the surface is wiped off with tissue paper, and the mass W (g) of the wet membrane is measured. Furthermore, the sample is dried under reduced pressure at 60° C. for 5 hours, and the weight D (g) of the sample after drying is measured. Based on the measured mass value, the water content of the cation exchange membrane is calculated according to the following formula. Moisture content (%) = 100 x (WD) / D
5. 3. The cation exchange membrane according to claim 1 or 2, An electrodialysis membrane for producing hydroiodic acid, wherein the porosity of the highly porous substrate is 20% or more and 90% or less, as measured according to the following procedure. (Procedure for measuring void ratio) A rectangular sample of X cm x Y cm is cut out from the highly voided substrate, and the thickness T (μm) of the sample is measured using a micro thickness gauge (terminal diameter Φ: 5 mm, measurement pressure: 62.47 kPa). The mass M (g) of the sample is measured separately, and these measurements and the density ρ (g / cm) of the resin material of the highly voided substrate are compared. 3 ) to calculate the porosity (%) of the highly porous substrate using the following formula. Porosity (%) = {1-(10000×M / ρ) / (X×Y×T)}×100
6. 3. The cation exchange membrane according to claim 1 or 2, The electrodialysis membrane for producing hydroiodic acid, wherein the electrodialysis apparatus is a bipolar membrane electrodialysis apparatus.
7. An electrodialysis apparatus for producing hydroiodic acid, comprising:
3. An electrodialysis apparatus comprising the electrodialysis membrane for producing hydroiodic acid according to claim 1 or 2 as a cation exchange membrane.
8. 8. The electrodialysis apparatus according to claim 7, The electrodialysis device is a bipolar membrane electrodialysis device.
9. 3. A method for producing hydroiodic acid, comprising a step of separating an aqueous iodide salt solution into hydroiodic acid and an aqueous hydroxide salt solution by using an electrodialysis apparatus comprising the electrodialysis membrane for producing hydroiodic acid according to claim 1 or 2 as a cation exchange membrane.
10. 10. The method for producing hydroiodic acid according to claim 9, the electrodialysis apparatus is a bipolar membrane electrodialysis apparatus, The bipolar membrane electrodialysis apparatus includes the cation exchange membrane, an anion exchange membrane, and a bipolar membrane disposed between the cation exchange membrane and the anion exchange membrane.
11. The method for producing hydroiodic acid according to claim 9 or 10, The method for producing hydroiodic acid, wherein the aqueous iodide salt solution is an aqueous solution containing at least one of an alkali metal iodide salt and an alkaline earth metal iodide salt.
Citation Information
Patent Citations
Recovering method for acid
JP1995000769A
Method for producing ion exchange membrane
JP2003012835A
Method for producing hydriodic acid
JP2009023847A
Method for recovering hydriodic acid from waste liquid
JP2011157237A
Bipolar membrane
JP2017190417A